Achieving National Health Insurance in Indonesia: Policies and Challenges - Ahmad Dwi Nuryanto; Turdialiev Mukhammad Ali Polatjon Ogli (Lembaga Contrarius Indonesia, 2025)
The regulation of contributions within Indonesia’s National Health Insurance scheme (Jaminan Kesehatan Nasional, JKN) continues to generate significant debate because it does not adequately embody the constitutional values of justice and social welfare. Health constitutes a fundamental human right and a core indicator of societal well-being that the state must actively guarantee. This study aims to analyze the fairness of JKN contribution policies, particularly their impact on independent Class III participants, and to evaluate the alignment of existing regulations with the state’s constitutional obligations. The research applies a normative juridical method, complemented by conceptual, philosophical, and systemic legal analysis, through the examination of statutory instruments and legal doctrines. The findings demonstrate that current JKN contribution regulations exhibit substantial deficiencies in legal substance, legal structure, and legal culture, as well as in their philosophical, sociological, economic, and normative foundations. These deficiencies cause an unequal distribution of financial burdens and place disproportionate pressure on participants with limited economic capacity. The study argues that policymakers must reconstruct the JKN contribution framework by positioning the state as the primary guarantor of public health insurance rather than merely an administrative regulator. The study concludes that recalibrating contribution levels, strengthening government subsidies, and reformulating regulations based on principles of humanity, utility, and social justice are essential to ensuring equitable, sustainable, and constitutionally grounded health insurance protection for all citizens.